Angiosarcoma of the Descending Aorta, Diagnostic Difficulties. (2016) - Anthonissen, N.; Menting, T.; Verkroost, M.; Morshuis, W.
Abstract : Introduction: Primary angiosarcomas of the aorta are rare and because of their non-specific presentation, the initial diagnosis is often very difficult. Report: A 66 year old woman, initially suffering from night sweats and general malaise, is presented. A computerized tomography (CT) scan was performed which showed a filling defect of the descending aorta. This defect later caused embolic occlusion of the celiac vessels. The patient underwent surgical resection of the filling defect of the descending aorta and an embolectomy of the celiac vessels. The defect was histopathologically diagnosed as an angiosarcoma. The clinical presentation, diagnostic pitfalls, histopathological diagnosis, and the therapeutic management are discussed. Discussion: In this case report, the importance of carefully diagnosing an angiosarcoma is highlighted as the consequences could be rapid metastasization or embolization. Highlights: An angiosarcoma of the descending aorta was diagnosed, which is a rare malignancy. This malignancy is very hard to diagnose therefore long-term survival is uncertain. This malignancy is very aggressive for both local and distant recurrence. This case report reflects the difficulty in diagnosing this malignancy. It also shows the rapid progression of this disease.